Hot Topics and Trends in Zero-Energy Building Research—A Bibliometrical Analysis Based on CiteSpace - Wei, Jia; Li, Jiyang; Zhao, Jiafan; Wang, Xiaoyang (Buildings (Basel), 2023)
With the development of a low-carbon economy, zero-energy structures will become prevalent and take center stage in the construction industry. This paper uses the CiteSpace software to create knowledge maps of authors, institutions and keywords, and then examined and commented on research publications regarding zero-energy buildings in order to understand the research state and development trends of zero-energy buildings. The findings demonstrate that: (1) Since its inception in 2000, research on zero-energy buildings has advanced significantly; (2) A subject analysis approach is used to identify development trends and research emphasis, and the four research areas with the most papers published are energy fuels, construction building technology, civil engineering and green sustainable science technology; (3) China, the United States and Italy are the countries with the most activity in zero-energy building research; (4) Out of the eight most prominent keywords for the study subjects, the design of zero-energy buildings, the estimation of the carbon emissions of zero-energy buildings, the technical challenges of zero-energy buildings and the follow-up energy-saving measures of zero-energy buildings are the four fundamental topics covered in the most cited papers; (5) There are three obstacles to the development of zero-carbon buildings: unclear standards, immature technology and insufficient development momentum. The following three problems should receive more attention in the future: how to develop a widely accepted zero-carbon building standard; how to coordinate national support to achieve technological breakthroughs; and the establishment of an effective incentive mechanism at the international and national levels to promote the development of zero-carbon buildings.